ANALISIS CEMARAN LOGAM BERAT KADMIUM (Cd) PADA KERANG BULU (Anadara inflate) di PERAIRAN TELUK AMBON - Rachmin Munadi; Asih Setiatin Lesilawang (Universitas Cokroaminoto Palopo)
The analysis has been carried out to determine the content of heavy metals cadmium (Cd) which contained on feather shells (Anadara inflate) at the Ambon bay waters. The samples of shells were weighed as much as 5 grams, charred and ingnited in a furnace at 500oC for 2 hours, then added 5 Ml of concentrated nitric acid and left for 24 hours. Put it in 50 mL volumetric flask with distilled water to the mark and filter it until a clear filtrateis abtained. Determination of the levels of Cr and Cd using an atomic absorption of spectorophotometer at the respective wavelengths of 283,2 nm and 228,9 nm, for Cr and Cd. The analysis o the results obtained Cd metel analysis results was 046 ppm. Based on the research results, it was found that in the three samples of shells from the waters of Ambon Bay, Cd metel had exceeded the threshold value (NAB) that had been set. The level of Cr metal contained in each shells originating from the waters of Ambon Bay has exceeded the threshold value (NAB) based on the decree of the State Minister for the Environmet (KMLH) IN 2004, for marine biota, namely 0,001 ppm.